(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article analyzes the results of research conducted at “IDEAL TEKSTIL-ORZU” LLC aimed at improving the production technology of outerwear made from natural leather. During the 2023–2025 research period, a new method of leather processing was developed, and the deformation characteristics of the products made using this method were studied experimentally. The results show that the new technology not only improves product quality, strength, and aesthetic performance but also provides significant economic benefits by reducing production costs. According to calculations, the production of 10,000 units per year yields an economic gain of 182.2 million UZS, with a specific efficiency of 18,220 UZS per product unit.